Pengaruh Layanan Transaksi dan Layanan Sebelum Pembelian Terhadap Keputusan Pembelian Melalui Pengalaman Navigasi Website Sebagai Variabel Intervening (Studi kasus pada Mahasiswa FISIP Undip Pengakses Website Bukalapak.com) - Zarkasi, Ilham Azmi; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2017)
ABSTRACTInternet users in Indonesia are growing every year. Along with the development of the Internet, the development of online shopping activities also evolved over time shifted some direct transaction activities. Increasing Internet users, has attracted various business ventures. With internet entrepreneurs can market the products offered indefinitely space and time. One of the online buying and selling websites is bukalapak.com which offers a wide range of daily necessities products to luxury items.This type of research is explanatory research, with a population of 100 respondents who have visited and made a purchase on the website bukalapak.com. Sampling in this study using non-probability sampling. The sampling technique uses Purposive sampling. Data were collected through questionnaires. Data analysis methods used using Partial Least Square (PLS) analysis, Mediation / Intervening Testing using Variance Accounted For (VAF) and Fit Model Indicators (Model of Indices) using WarpPLS 5.0.Based on the results of calculation analysis WarpPLS can be explained that the results of direct impact test on this research model shows the results of positive and significant influence. The result of indirect effect test on the model also shows the result of positive and significant influence. The effect of the website navigation experience as the mediating variable in the model is full mediation.Based on this, the researcher suggested to add and maximize the Operational System, Product Diversity, Placement of Menu Choices, and add variety of products offered by